Scalable Vision-based Gesture Interaction for Cluster-driven High Resolution Display Systems - Luo, Xun; Kenyon, Robert V. (2009 IEEE Virtual Reality Conference, 2009)
We present a coordinated ensemble of scalable computing techniques to accelerate a number of key tasks needed for vision-based gesture interaction, by using the cluster driving a large display system. A hybrid strategy that partitions the scanning task of a frame image by both region and scale is proposed. Based on this hybrid strategy, a novel data structure called a scanning tree is designed to organize the computing nodes. The level of effectiveness of the proposed solution was tested by incorporating it into a gesture interface controlling a ultra-high-resolution tiled display wall.